1994
DOI: 10.1002/bjs.1800810943
|View full text |Cite
|
Sign up to set email alerts
|

Pouch–vaginal fistula after restorative proctocolectomy: Aetiology and management

Abstract: Pouch-vaginal fistula is a rare complication following restorative proctocolectomy. Seven patients who developed such a fistula are presented. Six pouch-vaginal fistulas occurred at the level of the pouch-anal anastomosis and one 3 cm above the anastomosis, level with the posterior vaginal fornix. The anastomosis had been hand-sewn in four patients (following mucosectomy) and stapled in three. Five fistulas presented within the perioperative period (median 16 (range 10-30) days) and two at 186 and 273 days. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 5 publications
0
28
0
1
Order By: Relevance
“…Many procedures have been proposed for the treatment of PVF, 6,14,23,66 most of them adopted from rectovaginal procedures. [67][68][69][70][71][72] The reported success rates for these procedures in rectovaginal fistula repair have not been matched in PVF repair.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Many procedures have been proposed for the treatment of PVF, 6,14,23,66 most of them adopted from rectovaginal procedures. [67][68][69][70][71][72] The reported success rates for these procedures in rectovaginal fistula repair have not been matched in PVF repair.…”
Section: Treatmentmentioning
confidence: 99%
“…They reported total success in 11 of 14 patients (11/20 attempts), compared with a success rate of 5 of 20 patients for other local procedures in the same hospital. O'Kelly et al 6 reported successful repair in five of seven patients through use of an endovaginal approach. Some patients in these series required more than one attempt at transvaginal advancement before complete healing was achieved without difficulty or compromise to the sphincters.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a larger series of 59 patients, the internal opening was at the anastomosis in 37 and at the dentate line in 14 66 . Causative factors may include injury to the vagina or rectovaginal septum during the rectal dissection 66,67,69 or anastomotic dehiscence with pelvic sepsis 59,60,67 . The latter is probably the major predisposing factor as pelvic sepsis rates are significantly higher in patients with pouch-vaginal fistula than in those without 29,59,70,74 .…”
Section: Fistulation To the Vaginamentioning
confidence: 99%
“…1 The procedure eliminates the risk of cancer and preserves normal body image and route of defecation. However, some patients endure a long period of Postoperative morbidity in the form of recurrent pouchitis, 2 fistula formation, 3,4 and functional problems such as incontinence or anastomotic stricture with frequent bowel function. [5][6][7][8] Sometimes these problems lead to pouch excision and reconstruction of an ileostomy; the reported failure rate varies from 2 to 20 percent.…”
mentioning
confidence: 99%